Knowing You, Knowing Me (KYKM): an interactive game to address positive mother-daughter communication and relationships - Katsikitis, Mary; Jones, Christian; Muscat, Melody; Crawford, Kate (Frontiers in Psychology, 2014)
This technical report describes an interactive game environment designed to bring mothers and their adolescent daughters together to discuss three issues that have previously been shown in the literature to be of concern to families, as young girls transition from middle childhood to the adolescent years. The game is called Knowing you, Knowing me or KYKM, and is used to help mothers and daughters discuss the following three topics: positive communication skills, relationship building, and managing risky behaviours in the social environment. As the game remains untested, its limitations and future implications of its utility are discussed.